Characterization of Jinhua ham aroma profiles in specific to aging time by gas chromatography-ion mobility spectrometry (GC-IMS). (October 2020) - Liu, Dengyong; Bai, Lu; Feng, Xi; Chen, Yan Ping; Zhang, Danni; Yao, Wensheng; Zhang, Hao; Chen, Gaole; Liu, Yuan
Abstract: A rapid method for analyzing of Jinhua ham samples in different aging time was created based on gas chromatography-ion mobility spectrometry (GC-IMS). The GC-IMS chromatograph provided information regarding the identities and intensities of 37 volatile flavor compounds, including both monomers and dimers. Principal component analysis (PCA) effectively distinguished the variation in the aroma of the Jinhua ham s specific to aging time. Alcohol (octanol, 2-methylbutanol), ketones (2-butanone, 2-hexanone, 2-heptanone, acetoin, gamma-butyrolactone), aldehydes (butanal, 3-methylbutanal), ester (propyl acetate) and carboxylic acids (3-methylbutanoic acid) were considered as the main volatile compounds in the Jinhua ham samples . This GC-IMS method, then, proved to be feasible for the rapid and comprehensive detection of volatile compounds in Jinhua hams, and multivariance analysis (i.e.: PCA) was able to provide information related to aging time. Highlights: A rapid method for analyzing of Jinhua ham was created based on GC-IMS. GC-IMS provided information regarding the identities and intensities of volatiles. Alcohol, ketones, aldehydes, ester, and carboxylic acids were the main volatiles. GC-IMS proved to be feasible for the rapid and comprehensive detection of volatiles.